ಆಂಧ್ರಪ್ರದೇಶದಲ್ಲಿ ಬೌದ್ಧಧರ್ಮದ ಉಗಮ ಮತ್ತು ವಿಕಾಸ. - BYRAPPA M., (ಅಕ್ಷರಸೂರ್ಯ (AKSHARASURYA), 2023)
Original Telugu work: Andhradeshamlo Jaina, Bouddh Mataalu (Kannada Translation- Andhra Pradeshadalli Jaina Bouddha Dharmagalu) (In English: Jaina and Bouddha Religions in Andhra Pradesh); Original Author: Dr. B.S.L. Hanumantha Rao. He did valuable contributions to Telugu literature, especially in the field of Buddhism and Archaeology. The present work has its own importance in his important literary series. The reason why the translation of the present work is relevant is to raise awareness and validate the influence of Jainism and Buddhism, the major philosophical roots of India, in the southern states like Andhra and Karnataka; To understand the importance of philosophical movement across linguistic boundaries and cross-linguistic ties in ancient India to the phenomenon of linguistic territorialization of modern India; To review the unique contributions made by a regional base in shaping the theological and philosophical contours of all Indian Jain-Buddhism; The current Telugu version of the work contains many novelties. Hence the translation of this work is very important and relevant to cultural research between Kannada and Telugu.